2006
DOI: 10.1021/es060598w
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Removal Efficiency of Pharmaceuticals and Hormones in Different Treatment Processes of Source-Separated Urine with Bioassays

Abstract: Urine can be collected separately from the general wastewater with the aim of recycling the nutrients. Urine source-separation not only prevents wasting nutrients but also prevents potentially hazardous micropollutants from entering the wastewater stream and tainting a final fertilizer product. We assessed various urine treatment technologies for their performance to remove micropollutants such as pharmaceuticals, natural and synthetic steroid hormones, and their human biotransformation products. Removal effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 40 publications
0
59
0
1
Order By: Relevance
“…Escher et al (2009) assessed the efficiency of removal of toxicological activity by ozonation after secondary treatment using bioassays and compared that with removal using GAC. Escher et al (2006) estimated the removal efficiency of pharmaceuticals and hormones in separated urine using both bioassays and chemical analysis. This approach was extended to the ecotoxicological effects of polar micro-organics in effluent and receiving surface waters (Escher et al, 2008).…”
Section: Drinking Water Treatmentmentioning
confidence: 99%
“…Escher et al (2009) assessed the efficiency of removal of toxicological activity by ozonation after secondary treatment using bioassays and compared that with removal using GAC. Escher et al (2006) estimated the removal efficiency of pharmaceuticals and hormones in separated urine using both bioassays and chemical analysis. This approach was extended to the ecotoxicological effects of polar micro-organics in effluent and receiving surface waters (Escher et al, 2008).…”
Section: Drinking Water Treatmentmentioning
confidence: 99%
“…There are arguments about microbial risk, micro-pollutants, residual pharmaceuticals and hormones in urine (Höglund et al 2002;Escher et al 2006) and recommendation to store urine for more than 6 months at 20°C for hygienic aspects (Höglund et al 2002). But the storage of urine for months might not be very practical for poor people in Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…Urine source separation seems to be an efficient tool in wastewater management, because urine contains most of the nutrients as well as pharmaceutical contaminants but constitutes less than 1 % of the total wastewater volume (Larsen et al 2001(Larsen et al , 2004. Therefore a much smaller volume has to be treated and precipitation of struvite turns two dominant wastewater nutrients, nitrogen and phosphorus, into a slow release fertilizer (Escher et al 2006). Experiments with spiked urine showed that more than 98 % of the pharmaceuticals and hormones remained in solution during the precipitation process so that the product is almost free of most organic micro-pollutants (Ronteltap et al 2007;Escher et al 2006).…”
Section: Evaluation Of Technical Procedures To Remove Organic Contamimentioning
confidence: 99%
“…Therefore a much smaller volume has to be treated and precipitation of struvite turns two dominant wastewater nutrients, nitrogen and phosphorus, into a slow release fertilizer (Escher et al 2006). Experiments with spiked urine showed that more than 98 % of the pharmaceuticals and hormones remained in solution during the precipitation process so that the product is almost free of most organic micro-pollutants (Ronteltap et al 2007;Escher et al 2006).…”
Section: Evaluation Of Technical Procedures To Remove Organic Contamimentioning
confidence: 99%